Shiva Linga in the Garbhagriha of Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
A Shiva linga (aniconic representation of Shiva) is there at the centre of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple. Notably, the yonipatta (womb-shaped base) of the Shiva linga is square, deviating from the typical circular shape.